2002
DOI: 10.1016/s0378-5173(02)00178-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of topical cidofovir penetration using microparticles

Abstract: Cidofovir is a new class of antiviral agent with potent in vitro and in vivo activity against a broad spectrum of herpes viruses. The aim of this work was to obtain a prolonged therapeutic effect of cidofovir in the basal epidermis after its topical application. For this purpose, PLGA microparticles were prepared by solvent evaporation and spray-drying methods. Microparticles prepared by spray-drying showed a encapsulation efficiency of 80%.Conversely, for all the microspheres prepared by the W/O/W solvent eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 19 publications
3
13
0
1
Order By: Relevance
“…It has been also shown that PLGA microparticles could be used to deliver acyclovir into the basal epidermis (19). Similar results were obtained in some studies which were carried out with different drugs for topical delivery, such as cidofovir (20) and urea (13).…”
Section: Introductionsupporting
confidence: 72%
“…It has been also shown that PLGA microparticles could be used to deliver acyclovir into the basal epidermis (19). Similar results were obtained in some studies which were carried out with different drugs for topical delivery, such as cidofovir (20) and urea (13).…”
Section: Introductionsupporting
confidence: 72%
“…A previous study on the topical antiviral effect of cidofovirloaded microparticles (36) suggested the passage of the drug at higher concentrations to the first skin layers to an occlusive effect exerted by microparticles. That effect produced a film on the skin surface which reduced the transepidermal water loss and favored drug penetration into the skin.…”
Section: Histopathological Study Of Rabbit Skinmentioning
confidence: 97%
“…Various other systems have also been developed for delivery of active principles through the skin such as acyclovir-loaded poly(lactic-co-glycolic acid) (PLGA) topical microparticles (37)(38)(39), microsponges for topical delivery mupirocin (40), biodegradable PLGA microparticles in o/w and w/o cream (41), block copolymer nanoparticles (42), biodegradable nanoparticles (43), and PLA nanoparticles (44). Further, the strategies for vectorization of drug across the skin have been extended to polymeric gels like pluronic lecithin organogels (45), bioadhesive gels, etc.…”
Section: Introductionmentioning
confidence: 99%